Pengaruh Penguasaan Qawaid Terhadap Kemampuan Menulis Siswa Madrasah Aliyah YMPI Rappang - Herdah, Herdah; Jannah, Raodhatul; K, Abd. Rahman (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
Mastery of qawaid (Arabic grammar) is a fundamental component in Arabic language learning, particularly in supporting students’ writing skills. This study aims to examine the influence of qawaid mastery on students’ guided writing skills (insya' muwajjah) at Madrasah Aliyah (MA) YMPI Rappang. Guided writing refers to the ability to compose structured texts based on specific instructions or frameworks provided by the teacher. Using an ex post facto approach, the study involved a population of 113 eleventh-grade students, with a sample of 53 students selected through probability sampling using proportionate stratified random techniques. The sample size was determined using the Slovin formula. Data were collected through tests measuring students’ mastery of qawaid and their guided writing skills. Data analysis employed product-moment correlation and simple linear regression techniques. The results showed that qawaid mastery had a positive and significant influence on students' guided writing skills, with a coefficient value of 0.536. These findings indicate that strengthening Arabic grammar mastery contributes significantly to the development of guided writing abilities. Therefore, the integration of qawaid learning needs to be emphasized in the Arabic curriculum to support the optimal achievement of students’ writing competencies.